2016
DOI: 10.1371/journal.pone.0163638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pile Driving on the Residency and Movement of Tagged Reef Fish

Abstract: The potential effects of pile driving on fish populations and commercial fisheries have received significant attention given the prevalence of pile driving occurring in coastal habitats throughout the world. Behavioral impacts of sound generated from these activities on fish typically have a greater area of influence than physical injury, and may therefore adversely affect a greater portion of the local population. This study used acoustic telemetry to assess the movement, residency, and survival of 15 sheepsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…In line with these results, 23 we found several behavioral changes during and after the seismic survey period that can be attributed to acoustic disturbance. Cod gradually, but significantly, increased their distance to the nearest wind turbine after the sound exposure period compared to before and during exposure.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In line with these results, 23 we found several behavioral changes during and after the seismic survey period that can be attributed to acoustic disturbance. Cod gradually, but significantly, increased their distance to the nearest wind turbine after the sound exposure period compared to before and during exposure.…”
supporting
confidence: 89%
“…5,22 Moreover, if fish stay in an area despite a disturbance, there can still be behavioral and population-level effects. Iafrate et al, 23 for example, showed that resident reef fish that remained on site during pile-driving sounds were susceptible to behavioral effects during the exposure.…”
mentioning
confidence: 99%
“…The greater amount of (still very limited) data available on behavioural responses to impulsive sound comes from studies of pile driving sounds. Moreover, most of these behavioural studies have been conducted on captive fish, maintained in confined spaces (Herbert‐Read et al, ; Spiga et al, ), though a few recent studies have been conducted on fishes in the wild (Hawkins et al, ; Iafrate et al, ; Roberts et al, ). For example, Hawkins et al () observed the behaviour of schools of S. sprattus and S. scombrus in mid water at a quiet coastal location, using an echosounder.…”
Section: Effects Of Anthropogenic Soundmentioning
confidence: 99%
“…These investigations support the premise that certain species will be at greater risk to noise impacts than others, and even individuals or popula-tions within a species could show substantial variation in responses. Telemetry tagged sheepshead (Archosargus probatocephalus) showed no significant decrease in daytime residency or displacement during 35 days of pile driving at a wharf complex (Iafrate et al, 2016). Field studies of flatfish in US waters showed no effects from OWF construction pile driving or cable laying (Wilber et al, 2018).…”
Section: Effectsmentioning
confidence: 97%